1997
DOI: 10.1124/mol.52.3.491
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Activation by and Receptor Reserve for an Irreversible A1-Adenosine Receptor Agonist in DDT1MF-2 Cells and in Guinea Pig Heart

Abstract: SUMMARYThe p-and m-isothiocyanate adenosine derivatives N 6 - [4-[[[4-[[[[2-[[[(p-(m value for the radioligand to the remaining receptors. The relationship between irreversible A 1 -AdoR occupancy by p-DITC-ADAC and inhibition of cAMP accumulation revealed a relatively large receptor reserve (64%) for the maximal response. In guinea pig isolated hearts, m-DITC-ADAC (5 μM) prolonged the stimulus to His bundle (SH) interval by 2.1-fold; this response could be prevented by the antagonist 8-cyclopentyltheophylline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 26 publications
0
25
0
Order By: Relevance
“…Concerning the A 1 AR subtype, examples of covalent agents are reported and summarized in Figure 4 [40][41][42].…”
Section: Covalent Ligandsmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning the A 1 AR subtype, examples of covalent agents are reported and summarized in Figure 4 [40][41][42].…”
Section: Covalent Ligandsmentioning
confidence: 99%
“…In particular the N 6 substituted derivative of adenosine, named m-DITC-ADAC (4-isothiocyanatophenylaminothiocarbonyl, DITC; adenosine amine congener or (11), proved to be a good irreversible agonist for A 1 AR. It was able to mimic ischemic preconditioning in rabbits [40] and also prolong the stimulus of the His bundle (SA) interval by 2.1 fold in guinea pig isolated hearts [41].…”
Section: Covalent Ligandsmentioning
confidence: 99%
“…Previous studies have shown that A 1 AR‐mediated inhibition of cAMP accumulation in DDT cells is dominant over β 2 AR stimulation 3. 22 As these bivalent compounds have higher affinity and functional potencies for the A 1 AR over the β 2 AR, the lack of β 2 AR stimulation in the absence of DPCPX or with G protein‐uncoupled A 1 AR is likely due to their preferential binding to and activation of the inhibitory A 1 AR. Interestingly, all of the active bivalent compounds were full agonists at the A 1 AR, but partial agonists at the β 2 AR.…”
Section: Resultsmentioning
confidence: 70%
“…Receptor binding assays : The preparation of DDT 1 MF‐2 cell membranes and the ability of the test compounds to displace [ 3 H]‐8‐cyclopentyl‐1,3‐dipropylxanthine from the A 1 AR were determined as previously described 22. The ability of the test compounds to displace [ 125 I]‐(−)‐iodopindolol from the β 2 AR in the DDT cell membranes was determined as previously described 3.…”
Section: Methodsmentioning
confidence: 99%
“…It modulates physiological functions in heart and brain, regulates oxygen supply during cell stress, and is useful in the regulation renal function [2,3]. The amounts of adenosine in the urine and plasma samples can also be the marker of some diseases such as carcinoma or liver diseases [4].…”
Section: Introductionmentioning
confidence: 99%